Lightweight high-strength ceramsite concrete and preparation method thereof

By optimizing the formulation and preparation process of ceramic concrete, the problem of insufficient compressive strength of ceramic concrete is solved, strength improvement and construction performance improvement are achieved, its application range is expanded, and lightweight and thermal insulation properties are maintained.

CN119285305APending Publication Date: 2025-01-10广州兴业混凝土搅拌有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411473746.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Ceramic concrete is usually inferior to ordinary concrete in terms of mechanical properties, especially compressive strength, and limits its application in a wider range of fields.

Method used

Using a new formula and preparation process, including cement, mineral powder, fly ash, silicon powder, machined sand, ceramic granules, clean water, admixture and nano-silica modifier, through pretreatment, prewetting, and stirring , standstill and pumping steps to optimize the microstructure and construction performance of ceramic concrete.

Benefits of technology

It significantly improves the compressive strength and construction performance of ceramic concrete, making it exceed ordinary concrete in terms of strength and application range, maintains the lightweight and thermal insulation characteristics of ceramic concrete, while enhancing fire resistance, deformation resistance and carbonization resistance. ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285305A_ABST
    Figure CN119285305A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and discloses lightweight high-strength ceramsite concrete, which is prepared from the following raw materials in parts by weight: 380 to 420 parts of cement, 55 to 65 parts of mineral powder, 85 to 95 parts of fly ash, 18 to 22 parts of silicon powder, 560 to 600 parts of machine-made sand, 430 to 470 parts of ceramsite, 170 to 180 parts of clear water, 11.5 to 12.5 parts of additives and 5 to 7 parts of modifiers. According to the lightweight high-strength ceramsite concrete and the preparation method thereof, by adding the nano silicon dioxide modifier and optimizing the preparation process, a compact microstructure is formed, the compressive strength is remarkably improved, the standard of common concrete is reached or even exceeded, internal pores and bubbles are reduced through strict temperature control and a negative pressure standing technology, and the compactness is increased; the ceramsite concrete not only retains the characteristic of light weight of ceramsite concrete, but also makes a breakthrough in strength, and the application field of the ceramsite concrete is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, in particular to a lightweight high-strength ceramsite concrete and a preparation method thereof. Background Art

[0002] Due to its high deadweight and relatively low specific strength, traditional concrete has gradually exposed its limitations in modern construction applications, especially in special building structures that need to reduce structural deadweight, improve seismic performance or achieve large-span design. With the development of construction technology and the increasing complexity of structural design, these shortcomings of traditional concrete have become more prominent, leading to a growing demand for new materials.

[0003] As a lightweight material, ceramsite concrete has shown great potential in specific application scenarios due to its advantages such as low density and good thermal insulation performance. It can not only effectively reduce the dead weight of buildings, but also improve the thermal performance of buildings, which is conducive to energy conservation and emission reduction. However, despite these advantages, ceramsite concrete has poorer mechanical properties, especially compressive strength, which limits its application in a wider range of fields to a certain extent. Therefore, developing a new material that can maintain the lightweight characteristics of ceramsite concrete and reach or even exceed the level of ordinary concrete in strength has become one of the technical challenges that need to be solved urgently. Therefore, we proposed a lightweight and high-strength ceramsite concrete and a preparation method. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the deficiencies in the prior art, the present invention provides a lightweight and high-strength ceramsite concrete and a preparation method, proposes a new formula and preparation process, so that the ceramsite concrete can have higher strength while maintaining its lightness, and improves its pumping construction performance, thereby solving the problem that although ceramsite concrete has these advantages, its mechanical properties, especially compressive strength, are usually not as good as ordinary concrete, which to a certain extent limits its application in a wider range of fields.

[0006] (II) Technical solution

[0007] In order to achieve the above-mentioned purpose of proposing a new formula and preparation process, so that ceramsite concrete can have higher strength while maintaining lightness and improving its pumping construction performance, the present invention provides the following technical scheme: a lightweight and high-strength ceramsite concrete, comprising the following raw materials in proportion by weight: 380-420 parts by weight of cement, 55-65 parts by weight of mineral powder, 85-95 parts by weight of fly ash, 18-22 parts by weight of silica powder, 560-600 parts by weight of machine-made sand, 430-470 parts by weight of ceramsite, 170-180 parts by weight of clean water, 11.5-12.5 parts by weight of admixture and 5-7 parts by weight of modifier.

[0008] Preferably, the cement is 42.5 grade ordinary Portland cement; the fly ash is grade II fly ash, and the fineness is controlled below 30 microns; the fineness modulus of the machine-made sand is 2.6-2.8, and the mud content does not exceed 3%; the expanded clay is shale expanded clay; the clean water meets the drinking water standard; the admixture is a polycarboxylic acid high-performance water-reducing agent, and the water reduction rate is 25% to 30%; and the modifier is nano-silicon dioxide.

[0009] Preferably, the density of the ceramsite is less than 1000 kg per cubic meter, and the particle size is between 5 mm and 10 mm, and the 28-day compressive strength of the cement is not less than 42.5 MPa.

[0010] A method for preparing a lightweight high-strength ceramsite concrete, comprising lightweight high-strength ceramsite concrete, and further comprising the following steps:

[0011] S1, pretreatment: fly ash and cement are mixed evenly in a ratio of 200:125, and pretreated for 30 minutes;

[0012] S2. Pre-wetting the ceramsite: spray clean water to fully wet the surface of the ceramsite until the ceramsite reaches a saturated water state, but there is no free water on the surface;

[0013] S3, stirring: add the pre-treated fly ash, cement mixture, mineral powder, silica powder and machine-made sand into the mixer, start stirring, then gradually add water containing admixtures, and continue stirring until the water is completely integrated into the slurry to ensure that all components are evenly distributed;

[0014] S4. Adding ceramsite: adding the pre-wetted ceramsite into the mixer, and stirring by the slurry coating method to ensure that the ceramsite is evenly coated in the slurry;

[0015] S5. Adding modifier: After adding the ceramsite and stirring evenly, finally add the nano-silicon dioxide modifier and continue stirring for 1 minute to ensure that the modifier is evenly distributed;

[0016] S6. Standing: After mixing, the concrete is allowed to stand for 5 minutes to eliminate air bubbles;

[0017] S7. Pumping: Finally, the construction is carried out by using a pumping device with a set pressure of 10 to 20 Newtons per square centimeter.

[0018] Preferably, the ceramsite also includes a pre-wetting step before being added to the mixer, in which the surface of the ceramsite is fully moistened by spraying clean water to prevent the ceramsite from absorbing moisture in the concrete mixture and affecting the working performance and final strength of the concrete; the pre-wetting step should be completed before the ceramsite is added to the mixer, and ensure that there is no free water on the surface of the ceramsite.

[0019] Preferably, the mixer is a forced mixer with a stirring speed of 120 revolutions per minute; and during the stirring process, the temperature in the mixing drum is kept stable at 20±2 degrees Celsius.

[0020] Preferably, the standing step is carried out in an environment with a temperature of 20±2 degrees Celsius and a relative humidity greater than 50%, and negative pressure standing is adopted to more effectively remove bubbles.

[0021] Preferably, the pressure of the pumping equipment is set to 10 to 20 Newtons per square centimeter, and before pumping, the concrete is vibrated and screened to remove oversized particles to ensure a smooth pumping process.

[0022] (III) Beneficial effects

[0023] Compared with the prior art, the present invention provides a lightweight and high-strength ceramsite concrete and a preparation method thereof, which has the following beneficial effects:

[0024] 1. The lightweight high-strength ceramsite concrete and preparation method thereof, the prepared lightweight high-strength ceramsite concrete not only achieves lightweight, but also forms a denser microstructure inside the concrete due to the addition of nano-silicon dioxide modifier and optimized preparation process, effectively improving the compressive strength of the concrete. In addition, through strict temperature control and negative pressure standing and other means, the pores and bubbles inside the concrete are reduced, and the density of the concrete is further enhanced, so that the strength reaches or even exceeds the standard of ordinary concrete. Therefore, the present invention not only maintains the lightweight characteristics of ceramsite concrete, but also makes a breakthrough in strength, thereby expanding the application range of ceramsite concrete.

[0025] 2. The lightweight high-strength ceramsite concrete and preparation method thereof, the prepared lightweight high-strength ceramsite concrete not only maintains the characteristics of light weight and good thermal insulation performance of ceramsite concrete, but also significantly improves its mechanical properties, especially in terms of compressive strength, which reaches or even exceeds the level of ordinary concrete. In addition, through optimized preparation processes, such as pre-wetting ceramsite, controlling the temperature during mixing, negative pressure treatment under static conditions, and vibration screening before pumping, the pumping construction performance of the concrete is improved, and at the same time, the uniformity and density of the concrete are improved, and its fire resistance, thermal insulation, deformation resistance and carbonization resistance are further enhanced. This series of improvement measures enable the lightweight high-strength ceramsite concrete to have better comprehensive performance in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a schematic diagram of the preparation process of lightweight high-strength ceramsite concrete. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention and the accompanying drawings to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] See also Figure 1 A lightweight and high-strength ceramsite concrete comprises the following raw materials in proportion by weight: 380-420 parts by weight of cement, 55-65 parts by weight of mineral powder, 85-95 parts by weight of fly ash, 18-22 parts by weight of silica fume, 560-600 parts by weight of machine-made sand, 430-470 parts by weight of ceramsite, 170-180 parts by weight of clean water, 11.5-12.5 parts by weight of admixture and 5-7 parts by weight of modifier.

[0029] A method for preparing a lightweight high-strength ceramsite concrete, comprising lightweight high-strength ceramsite concrete, and further comprising the following steps:

[0030] S1, pretreatment: fly ash and cement are mixed evenly in a ratio of 200:125, and pretreated for 30 minutes;

[0031] S2. Pre-wetting the ceramsite: spray clean water to fully wet the surface of the ceramsite until the ceramsite reaches a saturated water state, but there is no free water on the surface;

[0032] S3, stirring: add the pretreated fly ash, cement mixture, mineral powder, silica powder and machine-made sand into the mixer, start stirring, then gradually add water containing admixtures, and continue stirring until the water is completely integrated into the slurry to ensure that all components are evenly distributed;

[0033] S4. Adding ceramsite: adding the pre-wetted ceramsite into the mixer, and stirring by the slurry coating method to ensure that the ceramsite is evenly coated in the slurry;

[0034] S5. Adding modifier: After adding the ceramsite and stirring evenly, finally add the nano-silicon dioxide modifier and continue stirring for 1 minute to ensure that the modifier is evenly distributed;

[0035] S6. Standing: After mixing, the concrete is allowed to stand for 5 minutes to eliminate air bubbles;

[0036] S7. Pumping: Finally, the construction is carried out by using a pumping device with a set pressure of 10 to 20 Newtons per square centimeter.

[0037] Furthermore, the cement is 42.5 grade ordinary Portland cement; the fly ash is grade II fly ash, and the fineness is controlled below 30 microns; the fineness modulus of the machine-made sand is 2.6-2.8, and the mud content does not exceed 3%; the expanded clay is shale expanded clay; the clean water meets the drinking water standard; the admixture is a polycarboxylic acid high-performance water-reducing agent, and the water reduction rate is 25% to 30%; and the modifier is nano-silicon dioxide.

[0038] Specifically, in the preparation of lightweight high-strength ceramsite concrete, 42.5-grade ordinary Portland cement is selected as the main cementitious material to ensure that the concrete has sufficient early strength and long-term stability; the fineness of Class I fly ash is controlled below 45 microns, which helps to improve the working performance of concrete, while reducing the amount of cement, giving the concrete good fluidity and filling properties; the fineness modulus of machine-made sand is between 2.6 and 2.8, and the mud content is controlled within 3%, ensuring good gradation of sand and improving the density and impermeability of concrete;

[0039] As a lightweight aggregate, shale expanded clay reduces the overall weight of concrete with its low density and good thermal insulation properties, while also giving the concrete excellent thermal insulation properties; using clean water that meets drinking water standards ensures that the quality of the concrete mixture is not polluted and is beneficial to the hydration reaction of the concrete; the water reduction rate of polycarboxylic acid high-performance water-reducing agent is between 25% and 30%, which can significantly reduce the water consumption of concrete, enhance the fluidity and workability of concrete, and at the same time improve the strength of concrete; as a modifier, nano-silica fills the tiny pores inside the concrete, promotes the growth of cement hydration products, and further improves the density and strength of the concrete.

[0040] Furthermore, the density of the expanded clay is less than 1000 kg per cubic meter, and the particle size is between 5 mm and 10 mm, and the 28-day compressive strength of the cement is not less than 42.5 MPa.

[0041] Specifically, the density of expanded clay is less than 1000 kilograms per cubic meter and the particle size is limited to 5 mm to 10 mm, which makes expanded clay concrete have a lighter deadweight and is suitable for construction projects that need to reduce the deadweight of the structure or achieve a large-span design; at the same time, this specification of expanded clay helps to improve the thermal insulation performance of concrete and further reduce the energy consumption of buildings; the 28-day compressive strength of cement is not less than 42.5 MPa, which ensures that expanded clay concrete has sufficient mechanical strength after the curing period and is suitable for structural parts with high load-bearing requirements; by selecting expanded clay of appropriate density and size and cement with sufficient strength, it is possible to maintain the lightweight characteristics of concrete while meeting the safety and durability requirements of the structure.

[0042] Furthermore, before adding the ceramsite to the mixer, a pre-wetting step is also included, in which the surface of the ceramsite is fully moistened by spraying clean water to prevent the ceramsite from absorbing moisture in the concrete mixture and affecting the working performance and final strength of the concrete; the pre-wetting step should be completed before the ceramsite is added to the mixer, and ensure that there is no free water on the surface of the ceramsite.

[0043] Specifically, in the preparation process of lightweight and high-strength expanded clay concrete, the expanded clay is pre-wetted before entering the mixer to ensure that the surface of the expanded clay is fully moistened; this measure can prevent the expanded clay from absorbing moisture in the concrete mixture during the mixing process, thereby avoiding the degradation of the working performance of the concrete and the damage to the final concrete strength due to the absorption of moisture by the expanded clay; the implementation of the pre-wetting step needs to be completed before the expanded clay is added to the mixer, and it must be ensured that there is no free water remaining on the surface of the expanded clay, which helps to maintain the moisture balance of the concrete mixture and ensure the quality and performance of the concrete.

[0044] Furthermore, the mixer is a forced mixer with a stirring speed of 120 revolutions per minute; and during the stirring process, the temperature in the mixing drum is kept stable at 20±2 degrees Celsius.

[0045] Specifically, in the preparation process of lightweight and high-strength expanded clay concrete, a forced mixer is used and the stirring speed is set to 120 revolutions per minute, which can ensure that all components are evenly distributed during mixing, avoiding differences in concrete performance caused by uneven mixing. At the same time, the temperature in the mixing drum is kept stable at 20±2 degrees Celsius during the stirring process, which helps to control the hydration reaction rate of the concrete and ensure the workability and strength of the concrete after hardening. By precisely controlling the stirring speed and temperature, the uniformity and stability of the concrete can be effectively improved, thereby ensuring the quality and construction performance of the final product.

[0046] Furthermore, the standing step is carried out in an environment with a temperature of 20±2 degrees Celsius and a relative humidity greater than 50%, and negative pressure standing is adopted to more effectively remove bubbles.

[0047] Specifically, in the preparation process of lightweight high-strength expanded clay concrete, the standing step is required to be carried out in an environment with a temperature of 20±2 degrees Celsius and a relative humidity greater than 50%, and negative pressure standing is used in order to more effectively remove bubbles in the concrete; this measure can reduce the pores inside the concrete and enhance the density of the concrete. By controlling the standing conditions, it not only helps to form a more uniform and stable concrete structure, but also can further improve the compressive strength and durability of the concrete. Negative pressure standing accelerates the escape of bubbles by creating a low-pressure environment, ensuring that the concrete expels excess air before hardening, thereby improving the overall quality of the concrete.

[0048] Furthermore, the pressure of the pumping equipment is set at 10 to 20 Newtons per square centimeter, and before pumping, the concrete is vibrated and screened to remove oversized particles to ensure a smooth pumping process.

[0049] Specifically, during the construction stage of lightweight and high-strength expanded clay concrete, the pressure of the pumping equipment is set at 10 to 20 Newtons per square centimeter, ensuring that the concrete can pass through the delivery pipeline smoothly and avoiding pumping interruptions due to insufficient pressure or pipeline damage caused by excessive pressure. Before pumping, the concrete is vibrated and screened to remove oversized particles to prevent them from clogging the pipeline or causing wear on the pumping equipment during the pumping process. The oversized particles are removed through vibration screening, which ensures the uniformity of the concrete, improves the pumping efficiency and construction quality, and ensures the smooth progress of the entire pumping process.

[0050] Specifically, firstly, the nano-silicon dioxide modifier, with its unique nano-scale size effect, plays a role in filling tiny pores inside the concrete, optimizing the microstructure of the concrete. This modifier can promote the growth of cement hydration products to form a denser microstructure, thereby significantly improving the compressive strength of the concrete. In this way, the present invention not only maintains the advantage of lightweight ceramsite concrete, but also achieves a breakthrough in strength, so that the final product reaches or even exceeds the standard of ordinary concrete;

[0051] Secondly, the present invention has also optimized the preparation process, such as pre-wetting expanded clay, controlling the temperature during stirring, negative pressure treatment under static conditions, and vibration screening before pumping. These optimization measures work together with the nano-silica modifier to make the lightweight high-strength expanded clay concrete not only have higher uniformity and density, but also enhance its fire resistance, heat preservation, deformation resistance and carbonization resistance. This series of improvements makes the lightweight high-strength expanded clay concrete have better comprehensive performance in practical applications.

[0052] In summary, the lightweight high-strength ceramsite concrete and preparation method, the prepared lightweight high-strength ceramsite concrete not only achieves lightweight, but also forms a denser microstructure inside the concrete due to the addition of nano-silicon dioxide modifier and optimized preparation process, effectively improving the compressive strength of the concrete. In addition, through strict temperature control and negative pressure standing and other means, the pores and bubbles inside the concrete are reduced, and the density of the concrete is further enhanced, so that the strength reaches or even exceeds the standard of ordinary concrete. Therefore, the present invention not only maintains the lightweight characteristics of ceramsite concrete, but also makes a breakthrough in strength, thereby expanding the application range of ceramsite concrete.

[0053] Moreover, the lightweight high-strength ceramsite concrete and preparation method thereof, the prepared lightweight high-strength ceramsite concrete not only maintains the characteristics of light weight and good thermal insulation performance of ceramsite concrete, but also significantly improves its mechanical properties, especially in terms of compressive strength, which reaches or even exceeds the level of ordinary concrete. In addition, through optimized preparation processes, such as pre-wetting ceramsite, controlling the temperature during mixing, negative pressure treatment under static conditions, and vibration screening before pumping, the pumping construction performance of the concrete is made better, while the uniformity and density of the concrete are improved, and its fire resistance, thermal insulation, deformation resistance and carbonization resistance are further enhanced. This series of improvement measures enables the lightweight high-strength ceramsite concrete to have better comprehensive performance in practical applications, and solves the problem that although ceramsite concrete has these advantages, its mechanical properties, especially compressive strength, are usually not as good as ordinary concrete, which to a certain extent limits its application in a wider range of fields.

[0054] The relevant modules involved in this system are all hardware system modules or functional modules that combine computer software programs or protocols with hardware in the prior art. The computer software programs or protocols involved in the functional modules are themselves technologies that are well known to those skilled in the art and are not improvements of this system. The improvements of this system are the interaction or connection relationships between the modules, that is, improvements to the overall structure of the system to solve the corresponding technical problems to be solved by this system.

[0055] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A lightweight high-strength ceramsite concrete, characterized in that: The invention comprises the following raw materials in proportion by weight: 380-420 parts by weight of cement, 55-65 parts by weight of mineral powder, 85-95 parts by weight of fly ash, 18-22 parts by weight of silica powder, 560-600 parts by weight of machine-made sand, 430-470 parts by weight of ceramsite, 170-180 parts by weight of clean water, 11.5-12.5 parts by weight of admixture and 5-7 parts by weight of modifier.

2. A lightweight high-strength ceramsite concrete according to claim 1, characterized in that: The cement is 42.5 grade ordinary Portland cement; the fly ash is grade II fly ash, and the fineness is controlled below 30 microns; the fineness modulus of the machine-made sand is 2.6-2.8, and the mud content does not exceed 3%; the expanded clay is shale expanded clay; the clean water meets the drinking water standard; the admixture is a polycarboxylic acid high-performance water-reducing agent, and the water reduction rate is 25% to 30%; and the modifier is nano silicon dioxide.

3. A lightweight high-strength ceramsite concrete according to claim 1, characterized in that: The density of the ceramsite is less than 1000 kilograms per cubic meter, and the particle size is between 5 millimeters and 10 millimeters. The 28-day compressive strength of the cement is not less than 42.5 MPa.

4. A method for preparing lightweight high-strength ceramsite concrete, characterized in that: The lightweight high-strength ceramsite concrete according to claims 1 to 3 further comprises the following steps: S1, pretreatment: fly ash and cement are mixed evenly in a ratio of 200:125, and pretreated for 30 minutes; S2. Pre-wetting the ceramsite: spray clean water to fully wet the surface of the ceramsite until the ceramsite reaches a saturated water state, but there is no free water on the surface; S3, stirring: add the pretreated fly ash, cement mixture, mineral powder, silica powder and machine-made sand into the mixer, start stirring, then gradually add water containing admixtures, and continue stirring until the water is completely integrated into the slurry to ensure that all components are evenly distributed; S4. Adding ceramsite: adding the pre-wetted ceramsite into the mixer, and stirring by the slurry coating method to ensure that the ceramsite is evenly coated in the slurry; S5. Adding modifier: After adding the ceramsite and stirring evenly, finally add the nano-silicon dioxide modifier and continue stirring for 1 minute to ensure that the modifier is evenly distributed; S6. Standing: After mixing, the concrete is allowed to stand for 5 minutes to eliminate air bubbles; S7. Pumping: Finally, the construction is carried out by using a pumping device with a set pressure of 10 to 20 Newtons per square centimeter.

5. A lightweight high-strength ceramsite concrete according to claim 4, characterized in that: Said S2, before adding the ceramsite into the mixer, the ceramsite surface is also wetted by spraying clean water to prevent the ceramsite from absorbing moisture in the concrete mixture and affecting the working performance and final strength of the concrete; The pre-wetting step should be completed before the expanded clay is added to the mixer, and ensure that there is no free water on the surface of the expanded clay.

6. The lightweight high-strength ceramsite concrete according to claim 4, characterized in that: In S2, the mixer is a forced mixer with a stirring speed of 120 revolutions per minute; and during the stirring process, the temperature in the mixing drum is kept stable at 20±2 degrees Celsius.

7. The lightweight high-strength ceramsite concrete according to claim 4, characterized in that: The step S5, the standing step, is performed in an environment with a temperature of 20±2 degrees Celsius and a relative humidity greater than 50%, and negative pressure is used to more effectively remove bubbles.

8. The lightweight high-strength ceramsite concrete according to claim 4, characterized in that: In S6, the pressure of the pumping equipment is set to 10 to 20 Newtons per square centimeter, and before pumping, the concrete is vibrated and screened to remove oversized particles to ensure a smooth pumping process.